2022
DOI: 10.3390/md20030202
|View full text |Cite
|
Sign up to set email alerts
|

Ulva (Enteromorpha) Polysaccharides and Oligosaccharides: A Potential Functional Food Source from Green-Tide-Forming Macroalgae

Abstract: The high-valued utilization of Ulva (previously known as Enteromorpha) bioresources has drawn increasing attention due to the periodic blooms of world-wide green tide. The polysaccharide is the main functional component of Ulva and exhibits various physiological activities. The Ulva oligosaccharide as the degradation product of polysaccharide not only possesses some obvious activities, but also possesses excellent solubility and bioavailability. Both Ulva polysaccharides and oligosaccharides hold promising pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…It was found that ulvan was mainly composed of rhamnose, iduronic acid, xylose, glucuronic acid, and a small amount of galactose, and the composition of the monosaccharide and the degree of sulfation varied with the species, harvest season, cultivation methods, growth environment, and extraction methods of Ulva sp. (Kidgell et al 2019;Ning et al 2022;Olasehinde et al 2019;Olsson et al 2020). Ulvan, as the main active component of Ulva sp., has a variety of biological activities, such as antiinflammatory (Kidgell et al 2020), anticoagulant (Faggio et al 2016), anti-tumor (Pradhan et al 2020), antioxidant (Pradhan et al 2022), anti-hyperlipidemia (Yuan et al 2018), immune regulation (Fernández-Díaz et al 2017), and plant growth-promoting activities (Shefer et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that ulvan was mainly composed of rhamnose, iduronic acid, xylose, glucuronic acid, and a small amount of galactose, and the composition of the monosaccharide and the degree of sulfation varied with the species, harvest season, cultivation methods, growth environment, and extraction methods of Ulva sp. (Kidgell et al 2019;Ning et al 2022;Olasehinde et al 2019;Olsson et al 2020). Ulvan, as the main active component of Ulva sp., has a variety of biological activities, such as antiinflammatory (Kidgell et al 2020), anticoagulant (Faggio et al 2016), anti-tumor (Pradhan et al 2020), antioxidant (Pradhan et al 2022), anti-hyperlipidemia (Yuan et al 2018), immune regulation (Fernández-Díaz et al 2017), and plant growth-promoting activities (Shefer et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has a wide range of application prospects in health food, agricultural feed, and fish–shrimp farming (Kidgell et al 2019 ). Ulvan is the main water-soluble sulfated polysaccharide existing in the cell wall of Ulva algae (Ning et al 2022 ; Zheng et al 2022 ). It was found that ulvan was mainly composed of rhamnose, iduronic acid, xylose, glucuronic acid, and a small amount of galactose, and the composition of the monosaccharide and the degree of sulfation varied with the species, harvest season, cultivation methods, growth environment, and extraction methods of Ulva sp.…”
Section: Introductionmentioning
confidence: 99%
“…Enteromorpha, a marine green macroalgal genus, has recently drawn the attention of researchers for biorefinery applications. Enteromorpha has important ecological and economic implications, as it serves as a food source and habitat for many marine organisms [32,33]. However, excess growth of Enteromorpha can also lead to negative environmental impacts, such as oxygen depletion and habitat degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, their biomass is composed of many sulfated polysaccharides containing glucose, xylose, glucuronic acid, galactose, and rhamnose [34,[37][38][39]. These polysaccharides show many bioactive functions such as anticoagulant activity, antioxidant activity, antitumor activity, and immunomodulatory activity [33,34,40,41]. Furthermore, the Enteromorpha hydrolysate has been reported in several studies as a potential substrate for production of biofuels and bioactive compounds [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Enteromorpha prolifera polysaccharide (EP) constitutes the main component of the cell wall and accounts for nearly 18% of the dry weight. It possesses various physiological properties such as antioxidant, anticoagulant, antitumor, antiaging, immune regulatory activities, elimination of inflammation, anti-tumor activity in skin cancer, skin-protective activities, and so on (Cao et al, 2020;Ning et al, 2022). Thus, EP holds a promising potential in the food industry as a new functional food, or as an additive in the cosmetics industry for natural products-based cosmeceuticals (Arokiarajan et al, 2022;Fernando et al, 2019).…”
Section: Introductionmentioning
confidence: 99%